Introduction of a non-conventional solution for Amazon transmission system: Analysis of the electric aspects - Pinto, A. J G; Costa, E. C M; Kurokawa, S. [UNESP]; Pissolato, J. (Institute of Electrical and Electronics Engineers (IEEE), 2011)
This article shows an analysis of the longitudinal electric parameters of a three-phase transmission line/section using a 280-meter high steel tower. This characteristic, the height of the line conductors and distance between them, are intrinsic related to the longitudinal and transversal parameters of the line. By this means, an accurate study was carried out in order to show the electric variations between a transmission line using the new technology and a three-phase conventional 440 kV line for a wide range of frequencies and a variable soil resistivity. In addition, by using a digital line model, simulations are carried out in time domain to analyze critical overvoltage transients on the studied line. © 2011 IEEE.
Keywords: electromagnetic transients; line parameters; steel towers; Transmission line; Digital line; Electric parameters; Electro-magnetic transient; Line conductors; Line parameters; Overvoltage transient; Soil resistivity; Time domain; Transmission systems; Computer simulation; Electric lines; Electric utilities; Time domain analysis; Transients; Transmission line theory; Engineering exhibitions